Avaliação da atenção primária à saúde na perspectiva dos usuários adultos do município de Juazeiro do Norte-Ceará - Rodrigues, Eduarda Maria Duarte (2018)
The Primary Health Care (PHC) instituted health as a fundamental and essential for the organization of health care, guided by the attributes of first access contact, longitudinality, coordination and integrality, family focus and community orientation. Scientific evidences have pointed to the benefits of PHC. However, there is a great heterogeneity in care, which results in health outcomes. In turn, as research to get the quality of program that has been important for the identification they are being provided, they also have as priority the problems of the health provider. The literature confirms a shortage of studies that seek the attributes of PHC, specially in the northeastern scenario and from the perspective of public health users. The presence and attributes of Primary Health Care, from the perspective of the adult users of the Municipality of Juazeiro do Norte-CE, were analyzed. This is an evaluative, quantitative and cross-sectional carried out 14 Basic Health Units of the city of Juazeiro do Norte-CE. Data collection took place in the total period from October 2016 to June 2017. Two data collections instruments were used: one to characterize the sociodemografic variable of the users; and another one, called Primary Health Care Assessment Tool (PCATool), to evaluate the quality of Primary Health Care. The dose size calculation was set at 50%, with significance of 5% (α=0,05) and relative sample error of 8%. Subsequently, the values were applied in the formula of infinite populations (n=115, 613), reaching a sample of “equal” size to 600 users, with a 10% increase to avoid losses and/or withdrawals, reaching the amount of 660, obtaining 47.14 users, rounded to 48 users per UBS. Ian the analysis, the process of doubling typing, description and data consolidation is used, through the SPSS (Statistical Package for Social Sciences), version 3.0. The results showed a prevalence of female adults, young, with low schooling and income. These participants attributed the worst evaluation to the attribute First Contact Access - Accessibility, with an average of 3,3 (±1,4), followed by Community Orientation, with an average of 3,8 (±2,3). Also, the attribute “Accessibility” was the one that received the lowest score, while the attribute “Coordination Integration of Care” was the best evaluated. There was a significant difference between the Health Districts, being the IV (rural area) and the VII (urban area) those who obtained, respectively, the worst and the best evaluation. The essential score (GS) reached the minimum average of 6.6 and the General Score (GS) was assigned score of 6.4. This value of the General Score represents that the Basic Health Units of Juazeiro do Norte are not providers of Primary Health Care, from the perspective of the users of health services. It is important to stress the need to promote between the PHC agents of municipality, to enhance the well-evaluated attributes, as well as to design intervention measures to improve those that received low scores.